Cross-border Tobacco Smuggling: Case Study of Eastern Macedonia and Thrace Region of Greece - Theologi, Vasiliki (Borders in Globalization Review, 2024)
This policy article examines tobacco smuggling as a manifestation of cross-border crime in the Eastern Macedonia and Thrace region of Greece. It explores the socio-economic and legal factors contributing to the phenomenon and provides insights from case studies and data analysis. Findings indicate that enhanced regional cooperation and stricter law enforcement measures are critical for combating this issue. The article suggests that a holistic, technology-driven, and collaborative approach is critical to combating this lucrative cross-border crime.